INTEGRATION OF PROJECT-BASED LEARNING METHODS IN ISLAMIC EDUCATION LEARNING TO BUILD STUDENTS' SOCIAL AWARENESS - Yusuf, M. Isa (PT. Antis International Publisher, 2024)
Objective: This study aims to explore the integration of the Project-Based Learning (PjBL) method in Islamic Religious Education (PAI) as a means to enhance students’ social awareness through contextual and participatory learning. Method: Employing a library research approach, the study analyzes secondary data collected from scholarly articles, books, and relevant documents using documentation techniques and content analysis. Results: The findings reveal that PjBL implementation in PAI actively engages students in projects that connect religious content with real-life social issues, thereby fostering meaningful and contextual learning. Project forms include social campaigns grounded in Islamic values, community service actions, and the development of educational media, all aimed at nurturing empathy, cooperation, and social responsibility. The integration of PjBL has demonstrated a positive impact on students’ environmental sensitivity, group collaboration, and application of Islamic values in daily life. Novelty: This study offers a significant contribution by positioning PjBL not merely as a cognitive strategy but as a holistic character-building approach that aligns Islamic teachings with social realities, highlighting its relevance for character education and contemporary pedagogical practices in religious learning.